Reversal of immunosuppression of lymphocyte proliferation caused by sera from persons with AIDS. - Tomar, R H (1995)
Sera from persons with AIDS contain inhibitors of lymphocyte proliferation. Inhibitory activity can be detected before the development of AIDS in humans. There appear to be at least three distinct suppressive moieties, one of which is prostaglandin E2. We and others had previously shown that serum samples from subjects with AIDS contained antibody to the cell line HUT 102B2. We attempted to remove this antibody and to determine if that action would also remove the inhibitory activity present in human immunodeficiency virus-positive sera. We incubated sera from subjects with AIDS with HUT 102B2 cells and tested the resultant supernatants for inhibition of cell proliferation. We found that this procedure significantly reversed inhibition by serum. Other cells and cell lines were similarly tested, but only HUT 102B2 cells absorbed the inhibitory product(s). However, we determined that secretory material from another cell line, MLA 144, also reversed inhibition. The physical characteristics of the supernatant were investigated. Thus, two procedures and likely separate products, possibly cytokines, reverse immunosuppression by sera from persons with AIDS.